Hubungan Personal Hygiene, Pengetahuan dan Pendidikan Penjamah Makanan Dengan Kualitas Makanan Secara Bakteriologis Escherichia Coli di Rumah Makan Pelabuhan Merak Banten Tahun 2023 - Siti Nur Ramdaniati; Heny Sasmita (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Food and beverage pollution can be caused by E. coli bacteria which is one of the main types of gram-negative species. In the process of food processing, the role of food security is very big. The purpose of this study is to look at the relationship between Personal Hygiene, knowledge and education of food handlers and bacteriological quality of E.coli. This type of research is analytic research, using a cross sectional approach with a sample of 32 food handlers at the Port of Merak. The tools used in data collection checks are questionnaire sheets, observation sheets and food bacteriological examinations. Data analysis was performed univariately and bivariately with the chi square test. The results of the study of 32 food samples found 50% of food contaminated by E. coli bacteria, 34.8% Personal Hygiene was not good and 56.2% of food handlers had low educational levels. Based on bivariate analysis there is a relationship between personal hyegine with (P value = 0.006). Suggestions from this research are holding and making efforts to increase the importance of knowledge about food handlers Personal Hygiene so as to avoid foodborne diseases or artborne foodborne disease and to supervise and provide guidance to sellers to improve food quality.